The Impact of Directive 2014/95/EU Implementation on Reliability of Non-Financial Information – Empirical Evidence from CEE Country - Łukasz MATUSZAK; Ewa RÓŻAŃSKA (Communications of International Proceedings, 2020)
Purpose: This study investigated the differences in the reliability of non-financial disclosure (NFD) across companies listed on the Warsaw Stock Exchange over the period surrounding the implementation of the Directive 2014/95/EU (Directive). Design/methodology/approach: To this purpose, we constructed a novel, hand‐collected NFD reliability index in line with the reporting requirements introduced by Directive. The sample comprised 71 selected listed companies over 6 years. Findings: The reliability of NFD have significantly increased over the years of analysis. The implementation of the Directive positively influenced the reliability of non-financial information. Originality: Our study contributes to the understanding of the impact of Directive on the NFD practices by European Union companies. Our research has important implications for policy makers because it revealed that mandatory regulations form a crucial instrument in improving the reliability of NFD. Our research suggests that, due to Directive, stakeholders should be provided with more reliable non-financial information.
Keywords: Reliability principle; credibility; CSR disclosure; Directive 2014/95/EU; non-financial disclosure; ESG disclosure; sustainability disclosure